2012
DOI: 10.4103/0971-9784.97973
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of a continuous noninvasive arterial pressure (CNAP™) monitor with an invasive arterial blood pressure monitor in the cardiac surgical ICU

Abstract: Accurate measurement and display of arterial blood pressure is essential for rational management of adult cardiac surgical patients. Because of the lower risk of complications, noninvasive monitoring methods gain importance. A newly developed continuous noninvasive arterial blood pressure (CNAP™) monitor is available and has been validated perioperatively. In a prospective study we compared the CNAP™ monitoring device with invasive arterial blood pressure (IAP) measurement in 30 patients in a cardiac surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The principle of NIRS has been widely used in various monitoring devices during cardiac surgery such as Swan-Ganz monitoring catheter, SpO 2 plethysmograph and continuous noninvasive arterial pressure smart pod. [ 17 ] Mespere VENUS 2000 CVP system which is used in this study to monitor CVPn is also based on NIRS technology. It uses single wavelength LED and PDs to detect changes in the blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of NIRS has been widely used in various monitoring devices during cardiac surgery such as Swan-Ganz monitoring catheter, SpO 2 plethysmograph and continuous noninvasive arterial pressure smart pod. [ 17 ] Mespere VENUS 2000 CVP system which is used in this study to monitor CVPn is also based on NIRS technology. It uses single wavelength LED and PDs to detect changes in the blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…This new technology has not been yet validated in the operating room for cardiac surgical patients though it has been validated in the post-operative cardiac surgical setting. [ 5 ] The present study was designed to compare systolic, diastolic and mean arterial pressure (MAP) values between CNAP and IAP during induction of general anaesthesia for different cardiac surgical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Given the possible damage caused by unregistered episodes of hypotension, but also the limitations in establishing invasive AP monitoring in the ED, a continuous noninvasive AP monitoring technology like the CNAP system might help to increase patient safety during the first hours of medical treatment. There already exist validation studies comparing CNAP-derived AP with invasively assessed AP measurements that reported clinically acceptable agreement for SAP, DAP, and MAP and, therefore, suggested CNAP as an alternative for invasive AP monitoring [5,8]. Furthermore, recent studies were able to demonstrate the potential value of continuous noninvasive AP monitoring by VUT using the CNAP device compared with intermittent oscillometric AP monitoring: Ilies and colleagues detected more hypotensive episodes after spinal anesthesia in women requiring caesarean section using the CNAP device than with the intermittent AP measurements [19].…”
Section: Discussionmentioning
confidence: 99%
“…The CNAP technology (CNSystems Medizintechnik AG, Graz, Austria) is one of two commercially available AP monitoring systems that use VUT. Previous studies have described its application during general anesthesia and showed clinically acceptable agreement between VUT using the CNAP technology and invasive continuous AP monitoring [5,7,8]. Furthermore, the CNAP technology was evaluated during medical procedures, e.g., interventional endoscopy [18] or spinal anesthesia for caesarean section [19].…”
Section: Introductionmentioning
confidence: 99%